The expressions of NGF and VEGF in the fracture tissues are closely associated with accelerated clavicle fracture healing in patients with traumatic brain injury - Zhang R; Liang Y; Wei S (Dove Medical Press, 2018)
Ran Zhang,1,2 Yi Liang,1 Shuxiang Wei1 1Department of Orthopedics, Liuzhou General Hospital, Liuzhou 545006, Guangxi, China; 2The Department of Orthopedics, The Affiliated Liuzhou General Hospital of Guangxi University of Technology, Liuzhou 545006, Guangxi, China Background: Angiogenesis and bone formation are vital for fracture healing. Nerve growth factor (NGF) not only promotes neuronal survival but also enhances the proliferation and differentiation of osteoblasts. Vascular endothelial growth factor (VEGF) plays an important role in angiogenesis. However, the potential correlation of NGF and VEGF levels with fracture healing in patients with traumatic brain injury (TBI) remains unclear.Methods: This study enrolled 22 patients with clavicle fracture and concomitant TBI (CFT group) and 25 patients with clavicle fracture alone (CF group). Serum NGF levels were measured with ELISA. The expressions of NGF, VEGF, and CD31 in callus tissues were measured with immunohistochemistry.Results: The fracture healing time in CFT group (82.22±13.61 days) was significantly shorter than that in CF group (127±25.05 days; P<0.001). The expression of CD31, marker of blood vessels, in callus tissues of CFT group was higher compared with that of CF group. Serum NGF levels and the expression of NGF in callus tissues of CFT group were higher than those in CF group (P<0.01). The expressions of CD31, NGF, and VEGF are correlated with shorter fracture healing time.Conclusion: The formation of blood vessels was increased in CFT group compared with CF group. NGF and VEGF levels were higher in CFT group than in CF group and correlated with shorter fracture healing time. Accelerated fracture healing in patients with TBI may be due to NGF- and VEGF-mediated angiogenesis at the fracture site. Keywords: traumatic brain injury, fracture healing, clavicle fracture, NGF, VEGF, angiogenesis